Phonological awareness skills of emergent bilingual Rumanyo-English learners - Karupu, Erwina Mushinga (Rhodes University, Faculty of Humanities, Department of Linguistics and Applied Language Studies)
This thesis is an account of a cross-sectional study which focused on investigating Phonological Awareness (PA) in emergent Rumanyo/English bilingual learners. PA and its contribution to reading fluency were investigated among 47 third grade learners with an average age of 9. 19, at a Namibian School, for which Rumanyo is the language of instruction and English, the first additional language. This cross-sectional study examines two levels of PA: Syllable awareness and phoneme awareness. Measures included three subtasks: identification, segmenting and deletion. Reading fluency was measured through oral reading fluency and silent reading. The findings suggest that learners' levels of PA are still developing with learners performing better on syllable awareness measures than on phoneme awareness. Reading fluency results evince low levels of proficiency in Rumanyo and in English, an average level of proficiency was recorded. To determine the relationship between PA and reading fluency, a Correlation Matrix was run and followed later with a linear regression. The findings demonstrate that syllable awareness predicted reading fluency in Rumanyo, whilst phoneme awareness did not show any association and as such, the model fit did not show any relationship either. With regards to English, neither syllables nor phonemes were a predictor of reading fluency. The study further examined to what extent the phonology of Rumanyo transferred to English.
Keywords: Phonological awareness; Grammar, Comparative and general -- Syllable; Phonemic awareness; Silent reading -- Ability testing; Diriku language; Emergent literacies